THE MEDIATING EFFECT OF FINANCIAL INCLUSION ON CASHLESS PAYMENT AND SMEs SUSTAINABILITY - Gainau, Paskanova Christi; Leatemia, Senda Yunita (Widya Mandala Surabaya Catholic University, 2024)
Research Purposes. This study aims to investigate the influence of cashless payment on micro, small, and medium enterprises sustainability.Research Methods. The sample used is a non-probability sample of 100 business actors in Ambon City with data analysis techniques, namely Structural Equation Modeling (SEM) through SmartPLS4 software to analyze the relationship between variables.Research Results and Findings. The findings show that cashless payment does not possess any direct correlation with MSMEs sustainability in Ambon. Furthermore, positive and significant correlation from cashless payment to MSMEs sustainability can be established through the mediatory of financial inclusion among the business owners. The result of this study generates enticing implications towards MSMEs which is SMES needs to have wide access to service and product of financial. It will promote improvement of SMES sustainability.